PENGARUH ENVIRONMENTAL, SOCIAL, AND GOVERNANCE DISCLOSURE TERHADAP NILAI PERUSAHAAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI (Studi Empiris Perusahaan Non-Keuangan di Bursa Efek Indonesia Tahun 2019-2021) - Ryan Edriansyah Adhi; Nur Cahyonowati (Diponegoro Journal of Accounting, 2023)
This study aims to examine the effect of environmental, social, and governance disclosure on firm value in non-financial companies in 2019-2021. Variable used in the examination are environmental, social, and governance disclosure as independent variable, firm value as dependent variable, and firm size as moderating variable. Research population is all non-financial companies listed on Indonesia Stock Exchange (IDX) in 2019-2021. The sampling techniques used purposive sampling and resulting 127 samples. The data analysis method used is moderation regression analysis method with SPSS 26 software. The result of this study shows that environmental, social, and governance disclosure has a significant positive effect on firm value. Firm size has a positive effect on firm value. Meanwhile, firm size can strengthen the relationship between environmental, social, and governance disclosure on firm value.